PENDAMPINGAN PENGEMBANGAN WEBSITE IBU DAN ANAK SEHAT DI DESA RAJAIYANG KECAMATAN LOSARANG KABUPATEN INDRAMAYU - Agustiyawan Agustiyawan; Heri Wibisono; Purnamadyawati Purnamadyawati; Fidyatul Nazhira; Farahdina Bachtiar; Rena Mailani; Elsa Mayranti; Padilah Febiyahna; Varsha Ravita; Muhamad Daffa Ramadhianto; Ananda Putri Rifanty (Jurnal Abdi Insani, 2023)
ABSTRACT Health development policies are directed at efforts to improve access and quality of health services towards universal health coverage with an emphasis on strengthening basic health services through increased promotive and preventive efforts supported by innovation and the use of technology. So that the next demographic bonus we get human resources (HR) that are superior and competitive. Efforts to support superior and competitive human resources can be started in the health sector by utilizing website technology so that the creation of smart villages is a necessity, especially in Rajaiyang Village, Indramayu Regency. The purpose of this program is to increase the fitness of mothers and children in Rajaiyang Village by developing a website towards a smart village. This community service method uses the ABCD (Asset-Based Community-driven Development) method. During the mentoring activities the participants were enthusiastic and gave a positive response. The conclusion of this service activity is that the delivery of material and website development assistance has contributed to improving the understanding and skills of the Rajaiyang Village community in improving fitness.